MENGENAL BUDAYA KRI TANJUNG KAMBANI SEBAGAI SARANA KOMUNIKASI ANTAR BUDAYA DALAM RANGKA SUKSESNYA TUGAS POKOK - Marwita, Paulin; Supriyono, Tjatur Supriyono (JURNAL ELEKTROSISTA, 2024)
As army officers, it is not uncommon for us to meet and interact with soldiers from other forces; who have traditions, doctrines and cultures that are different from ours. The comprehension to various cultures, traditions, doctrines and other forces cultures is necessary as a provision of knowledge for officers. One of the cultural forces discussed here is the culture on the Republic of Indonesia Warship (KRI) Tanjung Kambani. The culture at KRI is a representation of the culture of the Indonesian Navy. It is hoped that by getting to know of other forces cultures, understanding, respect and pride will arise; as well as a form of intercultural communication between fellow soldiers. An officer is expected to have good interpersonal skills and intercultural competence to provide knowledge for making decisions for the success of the main task and mitigating losses due to communication failures.